Changes in HIV testing policies and the implications for women. - Maman, Suzanne; King, Elizabeth (Journal of midwifery & women's health, 2008)
The US Centers for Disease Control and Prevention (CDC) and the World Health Organization (WHO) together with the Joint United Nations Programme on HIV/AIDS (UNAIDS) recently released new guidelines for HIV testing in health care settings. Both sets of guidelines recommend eliminating individual informed consent in favor of an opt-out approach that requires clients to actively decline the HIV test after a pretest information session. The revised guidelines also recommend reducing the amount of counseling that accompanies the HIV test. Women are more likely than men to be affected by efforts to expand access to HIV testing in health care settings because of women's increased vulnerability to HIV and greater contact with the health care system. Women may also be more susceptible to changes to the consent and counseling process for HIV testing because of their marginalized social status in many settings. More research is needed to document women's experiences with provider-initiated, opt-out HIV testing. Understanding women's experiences will help to formulate feasible and effective strategies to support women and ensure they gain access to HIV treatment services.
Keywords: Centers for Disease Control and Prevention (U.S.); Counseling; Female; Health Policy; HIV Infections; Human Rights; Humans; Informed Consent; Practice Guidelines as Topic; United Nations; United States; Women's Health; World Health Organization